Manajemen Perubahan Madrasah: Strategi Adaptif dalam Meningkatkan Mutu Pendidikan Islam di Madrasah Ibtidaiyah (MI) Muhammadiyah Rejang Lebong - Deli Susanti; Jumira Warlizasusi; Emmi Kholilah Harahap (IAIN Parepare, 2025)
This study analyzes adaptive change management strategies to improve the quality of Islamic education at Madrasah Ibtidaiyah (MI) Muhammadiyah Rejang Lebong, Bengkulu. The study addresses the empirical gap regarding the implementation of adaptive strategies in Islamic elementary schools, including transformational leadership, digital administration, stakeholder participation, human resource development, and change vision communication. A descriptive qualitative case study was conducted, collecting data through interviews, observation, and documentation, validated via source and method triangulation. Findings reveal the implementation of five key adaptive strategies, supported by organizational backing, enthusiastic young teachers, and strong internal communication, while obstacles include limited infrastructure and resistance from senior teachers. The adaptive strategies positively affect school quality, reflected in improved accreditation, increased public trust, and strengthened students’ Islamic character. The study highlights the necessity of systematic and Islamically grounded change management to enhance educational quality and the relevance of madrasahs in the modern era